Barents festivals and the development of local identity - Karlsen, Sidsel (Luleå tekniska universitet, Musik och dans, 2008)
The aim of the present study was to investigate how three specific music festivals, situated in the Barents region, contributed to development of local identity in their respective host municipalities. The aim was further explored through three research questions focussing on 1) how the festivals cooperated with local agents; 2) how the festivals participated in and contributed to processes of glocalisation; and 3) what kinds of stories that were told through the festivals about their respective host municipalities. The festivals investigated was the Festspel i Pite Älvdal (Sweden), the Festspillene i Nord-Norge (Norway) and the Jutajaiset Folklorefestivaali (Finland). The study was grounded in modernity theory as well as previous research on festivals' contribution to development of local identity. Concerning the methodological aspects of the study, it was designed using an embedded multiple case-design, in which each of the festivals constituted one case and the three research questions functioned as the cases' units of analysis. Hence, within-case as well as cross-case analysis was enabled. The empirical data consisted of field notes from participant observation of in all 58 festival events; interviews with the festivals' directors and official representatives of the festivals' host municipalities; and documentation in the form of festival programmes. The findings showed that all three festivals had extensive cooperation with a wide selection of local agents or stakeholders but also that the range and profoundness of this coopera tion seemed to depend on the festival management's awareness of and focus towards the necessity of building and maintaining stakeholder relationships. This awareness seemed further to depend on the festival's perceived self-identity, its degree of professionalism and institutional status. Regarding the participation in and contribution to processes of glocalisation, 17 aspects were found that were divided into the categories of reaching out; letting in; facilitating for meetings; and ...